Studien zum kaiserzeitlichen Tafelgeschirr aus Limyra - Yener-Marksteiner, Banu (Verlag der Österreichischen Akademie der Wissenschaften, 2020)
This book presents not only the spectrum of Roman imperial imported and local-regional tableware of the East Lycian city Limyra for the first time, but at the same time examines the tableware as a testimony of the material legacy of this Era, particularly with regard to sociocultural, socioeconomic and historical questions of the settlement.